ADJEKTIVA YANG MENYATAKAN MAKNA ‘MENTAL’ DALAM BAHASA BALI - Aridawati, Ida Ayu Putu (LPPM Universitas Dhyana Pura, 2021)
ABSTRAKPenelitian ini menggunakan pendekatan semantik untuk memberikan gambaranperbendaharaan konsep makna adjektiva dalam bahasa Bali. Masalah yang dibahas dalampenelitian ini adalah adjektiva yang menyatakan makna ‘mental’ dalam Bahasa Bali, yangmencakupi dua aspek, yaitu: (1) adjektiva yang menyatakan makna ‘suasana hati’ dan (2)adjektiva yang menyatakan makna ‘suasana pikiran’. Penelitian ini bertujuan memerikanadjektiva yang menyatakan makna ‘mental’ dalam Bahasa Bali. Dalam pengumpulan datadigunakan metode simak, dibantu dengan teknik pengartuan dan catat. Langkah berikutnyaadalah analisis data, menggunakan metode deskriptif sinkronis, dibantu dengan teknik analisiskomponen. Tahap selanjutnya adalah penyajian hasil analisis data, menggunakan metodeformal dan informal, dibantu dengan teknik induktif dan teknik deduktif. Berdasarkan hasilpembahasan, adjektiva yang menyatakan makna ‘mental’ dalam bahasa Bali memiliki 34leksem. Leksem tersebut terbagi dalam dua kelompok, yaitu 27 leksem yang menyatakanmakna ‘suasana hati’ dan 7 leksem yang menyatakan makna ‘suasana pikiran’. Leksem yangmenyatakan makna suasana hati dapat dibagi lagi menjadi dua, yaitu 10 leksem yangmenyatakan makna ‘suasana hati positif’ dan 17 leksem yang menyatakan makna ‘suasanahati negatif. Selanjutnya, tujuh leksem yang menyatakan makna ‘suasana pikiran’juga dapatdibagi menjadi dua, yaitu 2 leksem yang menyatakan makna ‘suasana pikiran positif’ dan 5leksem yang menyatakan makna ‘suasana pikiran negatif’.Kata Kunci: adjektiva, menyatakan makna ‘mental’, bahasa BaliABSTRACTThis study uses a semantic approach to provide an overview of the vocabulary of the conceptof adjective meaning in Balinese. The problems discussed in this study are adjectives thatexpress the meaning of 'mental' in Balinese, which includes two aspects, namely: (1) adjectivesthat express the meaning of 'mood' and (2) adjectives that express the meaning of 'state ofmind'. This study aims to describe adjectives that express the meaning of 'mental' in Balinese.In collecting data, the listening method was used, assisted by the technique of writing on cardsand taking notes. The next step is data analysis, using synchronous descriptive methods,assisted by component analysis techniques. The next stage is the presentation of the results ofdata analysis, using formal and informal methods, assisted by inductive and deductivetechniques. Based on the results of the discussion, adjectives that express the meaning of'mental' in Balinese have 34 lexemes. The lexemes are divided into two groups, namely 27lexemes which express the meaning of 'mood' and 7 lexemes which express the meaning of'state of mind'. The lexemes that state the meaning of mood can be further divided into two,namely 10 lexemes that state the meaning of 'positive mood' and 17 lexemes that state themeaning of 'negative mood'. Furthermore, 7 lexemes that state the meaning of 'state of mind'can also be divided into two, namely 2 lexemes that state the meaning of 'positive state of mind'and 5 lexemes that express the meaning of 'negative state of mind'.Keywords: adjective, express the meaning of 'mental', Balinese language